2021
DOI: 10.3390/healthcare9121712
|View full text |Cite
|
Sign up to set email alerts
|

A Machine Learning Approach to Predicting Diabetes Complications

Abstract: Diabetes mellitus (DM) is a chronic disease that is considered to be life-threatening. It can affect any part of the body over time, resulting in serious complications such as nephropathy, neuropathy, and retinopathy. In this work, several supervised classification algorithms were applied for building different models to predict and classify eight diabetes complications. The complications include metabolic syndrome, dyslipidemia, neuropathy, nephropathy, diabetic foot, hypertension, obesity, and retinopathy. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…e AdaBoost classifier algorithm was found to be highly accurate (0.917) for the prediction of diabetic nephropathy in a dataset of 884 patients and 70 attributes. When the attributes were decreased to the top 5 only, the performance was not affected [28]. Our results show that IBK and random tree classifiers with a dataset of 410 patients and 18 attributes achieved an accuracy of 93.6585%.…”
Section: Resultsmentioning
confidence: 76%
“…e AdaBoost classifier algorithm was found to be highly accurate (0.917) for the prediction of diabetic nephropathy in a dataset of 884 patients and 70 attributes. When the attributes were decreased to the top 5 only, the performance was not affected [28]. Our results show that IBK and random tree classifiers with a dataset of 410 patients and 18 attributes achieved an accuracy of 93.6585%.…”
Section: Resultsmentioning
confidence: 76%
“…Yazan Jian et al ( 2021) used a dataset from the Rashid Center for Diabetes and Research, which is situated in UAE and applied ML to predict diabetes disease. (Jian et al, 2021) Finally, Xue et al (2020) used SVM, NB and Light GBM, collected datasets from UCI ML Repository, and achieved the best accuracy with SVM. (Xue et al, 2020) In our work, we found that most diabetes disease predictions are based on gestational diabetes, which is present in pregnant ladies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another way, the authors of the paper [13] have built models to predict and classify diabetes complications. In this work, several supervised classification algorithms were applied to predict and classify 8 diabetes complications.…”
Section: Related Workmentioning
confidence: 99%